Step 1) Solve the first equation for x:
x + y = 5
x + y - color(red)(y) = 5 - color(red)(y)
x + 0 = 5 - y
x = 5 - y
Step 2) Substitute (5 - y) for x in the second equation and solve for y:
2x + y = 6 becomes:
2(5 - y) + y = 6
(2 * 5) - (2 * y) + y = 6
10 - 2y + y = 6
10 - 2y + 1y = 6
10 + (-2 + 1)y = 6
10 + (-1)y = 6
10 - 1y = 6
10 - y = 6
10 - color(red)(6) - y + color(blue)(y) = 6 - color(red)(6) + color(blue)(y)
4 - 0 = 0 + y
4 = y
y = 4
Step 3) Substitute 4 for y in the solution to the first equation at the end of Step 1 and calculate x:
x = 5 - y becomes:
x = 5 - 4
x = 1
The Solution Is:
x = 1 and y = 4
Or
(1, 4)